Op de roltrappen van het Tweede-Kamergebouw leden van het parlement. Van boven naar beneden en v.l.n.r.: Ruigrok, Kersten, Ockels, Swildens, Akkermans, Kalsbeek, Van Nieuwenhoven, Van Rijn, Beylen, Achttienribbe, Netelenbos, Van der Burg, Vliegenthart, Witteveen - Pejić, Maya
Op de roltrappen van het Tweede-Kamergebouw leden van het parlement. Van boven naar beneden en v.l.n.r.: Ruigrok, Kersten, Ockels, Swildens, Akkermans, Kalsbeek, Van Nieuwenhoven, Van Rijn, Beylen, Achttienribbe, Netelenbos, Van der Burg, Vliegenthart, Witteveen.